Concept and classification of powers of the Cyberpolice Department of the National Police of Ukraine - V. V. Bereza (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article has outlined the etymology of the legal category of “powers”. Special attention has been focused on the fact that, revealing the essence of the powers of the Cyberpolice Department as a subject of counteraction to cybercrime, such concepts as “right” and “duty” can not be evaded. The author has made the conclusion about the interdependence of the terms of “powers” and “task”. It has been noted that the term of “powers of the Cyberpolice Department of Ukraine” did not receive its legislative consolidation.